CONTINUITY, TRANSFORMATION, AND IDENTITY IN KAZAKH LITERATURE: A HISTORICAL AND THEMATIC ANALYSIS - R. Kenjebaeva (Modern American Journals, 2025)
Kazakh literature represents a historically layered cultural system shaped by oral tradition, social transformation, and evolving national consciousness. Emerging from the nomadic worldview of the Eurasian steppe, it developed first through oral epic and poetic forms and later through written genres influenced by colonial encounters, national awakening movements, Soviet ideological frameworks, and post-independence cultural reorientation. This article offers a historical and thematic analysis of Kazakh literature from its oral foundations to contemporary literary practices. Special attention is paid to the concepts of continuity and transformation, examining how traditional aesthetic principles, ethical values, and narrative strategies are preserved, reinterpreted, and reshaped across different historical periods. The study argues that Kazakh literature functions not only as an artistic system but also as a key medium for constructing cultural identity, collective memory, and responses to modernity and globalization.
Keywords: Kazakh literature, oral tradition, national identity, cultural continuity, literary transformation, postcolonial discourse